Kapok Seed Separator Machine - Mohammad Noor, Hafsa (Multidisciplinary Applied Research and Innovation, 2023)
Kapok is a silky fiber that obtained from the pods of the kapok tree. It highly use for pillows, mattresses, toys, upholstery, insulation material, and as a substitute for absorbent cotton in surgery. Kapok is also naturally hypoallergenic, anti-microbial, and dust mite resistant that can overcome the health issues such as bacteria breed and skin diseases. Kapok pillows get high demand because of the beneficial usage of the kapok and its lifespan. Traditional method to separate seed from kapok are used bare hands or beat using wooden bamboo stick. However, there are lack in the safety and health issue when using the traditional methods to make kapok pillows that may lead to itching and harm. The improper equipment also needs to be concerned because the process required blade rods composed of seed and stem. The difficulty in obtaining technical devices due to the high cost of maintenance and acquisition of these machines, which does not match to consumer money. Inadequate labour to complete the kapok filling process. In this study, Kapok Machine is fabricated in order to evaluate the cleanliness of kapok after the separation process and increase the speed of kapok pillow production. Electric motor and blower are used to separate aside the seed and kapok and instantly fill up the pillowcase with the well-separated kapok. As has been demonstrated, the Kapok Machine require only 11 minutes to complete the process of making kapok pillow. The number production for 1 kg kapok that can be done is 6 pieces. The design of this Kapok Machine ensured can assist SME to produce technologies that can reduce the risk of injury to employees during the process of seed separation from kapok and increase the speed of kapok pillow